2014
DOI: 10.4172/2161-0460.1000161
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits of Cognitive Stimulation or Training/Rehabilitation upon Brain Function as an Efficacious Treatment for Diagnosed Dementia or Mild Cognitive Decline

Abstract: Medication has had disappointing results seen in various recently failed drug trials.The role of medication has typically been more preventative as opposed to providing evidence of improved memory function reported by cognitive rehabilitation research. The interest held by our facility is based upon fifteen years of providing cognitive training and seeing some type of improvement in every patient following as minimal as three months of training (twice weekly for one hour).Differences are seen on neuropsycholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
(21 reference statements)
0
4
1
Order By: Relevance
“…or they did not even consider the subdomains at all. These inconsistent details of past reports [7,8,13,14] make it difficult to compare our results with those of previous studies.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…or they did not even consider the subdomains at all. These inconsistent details of past reports [7,8,13,14] make it difficult to compare our results with those of previous studies.…”
Section: Discussioncontrasting
confidence: 90%
“…Sherman et al [14] reported that the specific focus of the program's content appears to be a much stronger predictor of improved functioning than the duration, number of sessions, and length. Fisher [8] reported that the effectiveness and durability of interventions improved targeted cognitive abilities even despite training that was limited in time as well as number of training sessions. The results of these prior studies show that although the duration and number of sessions in the present study was not enough, the effects on the target capacitiesdvisuospatial/executive ability and memorydwere meaningful, while effects on (non-targeted) endurance and abstractive ability were less so.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this vein, cognitive stimulation programs have adopted multiple forms and approaches, ranging from scientific interventions based on neuroplasticity (Nahum et al, 2013) and cognitive constructs (Jaeggi et al, 2008) or approaches inspired by meditation practices (Tang et al, 2007), to more gamified interventions (Anguera et al, 2013), or to commercial videogames originally designed for other purposes (Green and Bavelier, 2003). This diversity of target populations and approaches has been partially responsible for the controversy on the reproducibility and generalizability of the results obtained across studies and on the effectiveness of cognitive stimulation programs [see Fisher (2014)].…”
Section: Cognitive Stimulation and Brain Training: Concept And Effectivenessmentioning
confidence: 99%
“…He reports that he feels that he can rely more upon his memory for daily life tasks. This case study is commensurate with ongoing research and improvement seen over the course of the last ten years, shown in abstracts presented at area conferences since 2012 by this facility [10][11][12][13][14][15][16][17][18].…”
Section: Journal Of Neurology and Neurophysiologymentioning
confidence: 99%